Cuidados de enfermería en la prevención de infecciones en recién nacidos del Hospital General Martin Icaza Babahoyo octubre 2018 - abril 2019 - Macias Muñiz, Kelly Kimberly (2019)
Neonatal infections can occur prior to birth or at birth even within the first forty-eight hours. The consequences of the infection develop according to the infectious agent or acquired bacteria. NICU services establish an area of great care within the hospital because it houses children with different pathologies with risk factors. The vast majority of neonatal deaths originate in low and middle income countries. The survival and health of the newborns can be optimized and the number of prenatal deaths can be reduced by taking as a priority a high responsibility for effective newborn care, delivery care by competent personnel, postnatal surveillance for mothers and newborns, and care of newborns at risk of sepsis. Nursing care in the neonatal stage is of paramount importance for the prevention of postnatal infections. The prevention by nursing staff at the Martin Icaza General Hospital has become a challenge. However, we cannot omit that neonatal sepsis is a normal cause of infant morbidity and mortality, the use of aggressive therapies in time and broad-spectrum antibiotics that are provided to each case that is accompanied by the neonatal intensive care unit, Mortality remains unacceptably high especially in preterm infants. However, there are many disadvantages that hinder the tranquility of newborns, without reaching serious diseases or at least requiring treatment. In such a case, it is always important to attend to any unusual condition, because they are so small that it can be annoying or dangerous.